2017
DOI: 10.1105/tpc.17.00287
|View full text |Cite
|
Sign up to set email alerts
|

The F-Box Protein ZYGO1 Mediates Bouquet Formation to Promote Homologous Pairing, Synapsis, and Recombination in Rice Meiosis

Abstract: Telomere bouquet formation, a highly conserved meiotic event, plays an important role in homologous pairing and therefore progression of meiosis; however, the underlying molecular mechanism remains largely unknown. Here, we identified ZYGOTENE1 (ZYGO1), a novel F-box protein in rice (Oryza sativa), and verified its essential role in bouquet formation during early meiosis. In zygo1 mutants, zygotene chromosome aggregation and telomere clustering failed to occur. The suppressed telomere clustering in homologous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 57 publications
1
44
0
Order By: Relevance
“…In interphase, telomeres often clustered to form a single speckle ( Figure 1C). A similar conformation, called a ''bouquet,'' has been reported in meiotic maize, wheat, and rice cells [27][28][29]. However, in contrast to bouquet conformation described in flowering plants, the telomere gathering in Marchantia nuclei did not display a specific association of telomeres with the nuclear periphery ( Figure 1C).…”
Section: Telomeres Centromeres and Overall Nuclear Organizationsupporting
confidence: 71%
“…In interphase, telomeres often clustered to form a single speckle ( Figure 1C). A similar conformation, called a ''bouquet,'' has been reported in meiotic maize, wheat, and rice cells [27][28][29]. However, in contrast to bouquet conformation described in flowering plants, the telomere gathering in Marchantia nuclei did not display a specific association of telomeres with the nuclear periphery ( Figure 1C).…”
Section: Telomeres Centromeres and Overall Nuclear Organizationsupporting
confidence: 71%
“…Several F-box proteins, putatively interacting in the SCF E3 ubiquitin ligase complex, also displayed differential expression throughout prophase I. In rice, mutations in two F-box proteins interacting with the ASK1 equivalent OSK1, MOF and ZYGO1, have also been shown to result in male sterility (He et al , 2016; Zhang et al , 2017). Several genes annotated as SINA E3 ligases also displayed differential expression during prophase I.…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis pachytene checkpoint 2 (pch2 ) and pollen semisterility 1 (pss1 ) mutants, HEI10 or MutL Homolog 1 (MLH1) foci (marking mature CO sites) were associated only with stretches of SC (Duroc et al, 2014;Lambing et al, 2015). Recently, it was reported that rice ZYGOTENE1 (ZYGO1) promotes homologous pairing, synapsis and CO formation by mediating bouquet formation (Zhang et al, 2017). In these mutants, double-strand break (DSB) formation and early recombination intermediates are successfully established, whereas the intermediates do not mature into COs.…”
Section: Oshop2 Provides a Link Between Homologous Recombination Andmentioning
confidence: 99%